“Arming half-baked people with weapons!” Information enclaving among professionals and the need for a care-centred model for antibiotic use information in Uganda, Tanzania and Malawi - Susan Nayiga; Eleanor E MacPherson; John Mankhomwa; Fortunata Nasuwa; Raymond Pongolani; Rita Kabuleta; Mike Kesby; Russell Dacombe; Shona Hilton; Delia Grace; Nicholas Feasey; Clare I.R. Chandler (Global Health Action)
Background The overuse of antimicrobial medicines is a global health concern, including as a major driver of antimicrobial resistance. In many low- and middle-income countries, a substantial proportion of antibiotics are purchased over-the-counter without a prescription. But while antibiotics are widely available, information on when and how to use them is not. Objective We aimed to understand the acceptability among experts and professionals of sharing information on antibiotic use with end users – patients, carers and farmers – in Uganda, Tanzania and Malawi. Methods Building on extended periods of fieldwork amongst end-users and antibiotic providers in the three countries, we conducted two workshops in each, with a total of 44 medical and veterinary professionals, policy makers and drug regulators, in December 2021. We carried out extensive documentary and literature reviews to characterise antibiotic information systems in each setting. Results Participants reported that the general public had been provided information on medicine use in all three countries by national drug authorities, health care providers and in package inserts. Participants expressed concern over the danger of sharing detailed information on antibiotic use, particularly that end-users are not equipped to determine appropriate use of medicines. Sharing of general instructions to encourage professionally-prescribed practices was preferred. Conclusions Without good access to prescribers, the tension between enclaving and sharing of knowledge presents an equity issue. Transitioning to a client care-centred model that begins with the needs of the patient, carer or farmer will require sharing unbiased antibiotic information at the point of care.